MENTAL WELL-BEING OF GRADUATE SCHOOL STUDENTS OF THE NUEVA VIZCAYA STATE UNIVERSITY: ITS CORRELATION WITH COPING STRATEGIES - Noel V. Sadinas; MARJORIE B. GOMEZ- SIMPLICIANO; WILHELMINA C. BULLECER, PhD (International Journal of Educational Excellence and Innovation, 2025)
This study examines the coping strategies and mental well-being of 77 graduate school students from the College of Teacher Education at Nueva Vizcaya State University for the academic year 2024-2025. Employing a quantitative research design using the descriptive-correlational method, data were collected through structured questionnaires and analyzed using statistical procedures such as mean, analysis of variance (F-test), and Pearson-r correlation, with hypotheses tested at a 0.05 level of significance. Findings indicate that the overall mental well-being of graduate students is generally positive, with social and professional well-being rated as very good, while emotional and physical well-being received the lowest ratings of good. coping strategies were found to be effective, with a strong preference for focus on positives and support coping, while evasive coping was the least utilized. Statistical analyses reveal no significant differences in mental well-being and coping strategies across academic programs, suggesting that students experience similar challenges and employ comparable coping mechanisms. Furthermore, no significant relationship was found between mental well-being and coping strategies, indicating their independence. Based on these insights, a training program was developed to enhance key areas of well-being and coping, ensuring sustained support for students' academic and personal resilience.